Comparative Analysis of Shear Bond Strength between Orthodontic Brackets Adhered Using Self-Etching Adhesives and Conventional Adhesives - Shekhar K. Asarsa; Mansi Mehta; Manisha Tripathi; Perala Johnson; Mandeep Shilpi; Sukruthi Vengala (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: The strength of the connection between orthodontic brackets and the enamel is a major factor in the outcome of orthodontic therapy. Bonding methods have changed a lot, and self-etching primers are becoming more and more common because of their easy process. Materials and Methods: Two sets of 40 removed human premolars (n = 20) were randomly assigned. Group B used a self-etching adhesive system, while Group A used a traditional adhesive method that included acid etching using 37% phosphoric acid. A consistent bonding approach was used to attach brackets to every sample, and thermocycling (500 cycles between 5°C and 55°C) was then performed. A universal testing machine was used to test the shear bond strength (SBS) at a crosshead speed of 1 mm/min. Using a stereomicroscope, the adhesive remnant index (ARI) was assessed. Results: Group B (self-etching adhesive) had a mean SBS of 12.7 ± 1.8 MPa, while Group A (traditional adhesive) had a mean SBS of 15.2 ± 2.1 MPa. There was a statistically significant change (P < 0.05). Group A exhibited more enamel retention than Group B, according to ARI ratings. Both adhesives, however, offered sufficient SBS for clinical use. Conclusion: Self-etching adhesives provided sufficient bond strength for orthodontic applications with the benefit of a streamlined bonding process, while traditional adhesives demonstrated better SBS. Clinical effectiveness and patient requirements should be taken into account while choosing between these systems.